Evaluating the Utility and Constraints of the Competitive Counter Flow (CCF) Assay in OATP1B1 Substrate Profiling - Sumathy Mathialagan; Mark A. West; Emi Yamaguchi; Hannah M. Moulton; Brendon Kapinos; Sasan Paryad Zanjani; David A. Tess; Emi Kimoto; Manthena V. S. Varma; Sook Wah Yee (The AAPS Journal, 2026)

Utilization of Rosuvastatin and Endogenous Biomarkers in Evaluating the Impact of Ritlecitinib on BCRP, OATP1B1, and OAT3 Transporter Activity - Yeamin Huh; Anna Plotka; Hua Wei; Julia Kaplan; Nancy Raha; Justin Towner; Vivek S. Purohit; Martin E. Dowty; Robert Wolk; Manoli Vourvahis; Amanda King-Ahmad; Sumathy Mathialagan; et al. (Pharmaceutical Research, 2023)
Purpose Ritlecitinib, an inhibitor of Janus kinase 3 and tyrosine kinase expressed in hepatocellular carcinoma family kinases, is in development for inflammatory diseases. This study assessed the impact of ritlecitinib on drug transporters using a probe drug and endogenous biomarkers. Methods In vitro transporter-mediated substrate uptake and inhibition by ritlecitinib and its major metabolite were evaluated. Subsequently, a clinical drug interaction study was conducted in 12 healthy adult participants to assess the effect of ritlecitinib on pharmacokinetics of rosuvastatin, a substrate of breast cancer resistance protein (BCRP), organic anion transporting polypeptide 1B1 (OATP1B1), and organic anion transporter 3 (OAT3). Plasma concentrations of coproporphyrin I (CP-I) and pyridoxic acid (PDA) were assessed as endogenous biomarkers for OATP1B1 and OAT1/3 function, respectively. Results In vitro studies suggested that ritlecitinib can potentially inhibit BCRP, OATP1B1 and OAT1/3 based on regulatory cutoffs. In the subsequent clinical study, coadministration of ritlecitinib decreased rosuvastatin plasma exposure area under the curve from time 0 to infinity (AUC inf ) by ~ 13% and maximum concentration (C max ) by ~ 27% relative to rosuvastatin administered alone. Renal clearance was comparable in the absence and presence of ritlecitinib coadministration. PK parameters of AUC inf and C max for CP-I and PDA were also similar regardless of ritlecitinib coadministration. Conclusion Ritlecitinib does not inhibit BCRP, OATP1B1, and OAT3 and is unlikely to cause a clinically relevant interaction through these transporters. Furthermore, our findings add to the body of evidence supporting the utility of CP-I and PDA as endogenous biomarkers for assessment of OATP1B1 and OAT1/3 transporter activity.

Estimation of the Effect of OAT2-Mediated Active Uptake on Meloxicam Exposure in the Human Liver - Rui Li; Sumathy Mathialagan; Jonathan J. Novak; Heather Eng; Keith Riccardi; John Litchfield (The AAPS Journal, 2020)

Erratum to: Reliable Rate Measurements for Active and Passive Hepatic Uptake Using Plated Human Hepatocytes - Yi-an Bi; Renato J. Scialis; Sarah Lazzaro; Sumathy Mathialagan; Emi Kimoto; Julie Keefer; Hui Zhang; Anna M. Vildhede; Chester Costales; A. David Rodrigues; Larry M. Tremaine; Manthena V. S. Varma (The AAPS Journal, 2017)

Reliable Rate Measurements for Active and Passive Hepatic Uptake Using Plated Human Hepatocytes - Yi-an Bi; Renato J. Scialis; Sarah Lazzaro; Sumathy Mathialagan; Emi Kimoto; Julie Keefer; Hui Zhang; Anna M. Vildhede; Chester Costales; A. David Rodrigues; Larry M. Tremaine; Manthena V. S. Varma (The AAPS Journal, 2017)